Defending Culture - Fornäs, Johan. author. aut Link
VIII, 256 p. 1 illus.
Keywords: This book concerns the implications and interrelations of key concepts of culture, defending an updated communicative notion of culture as meaning-making against a series of current challenges. The first part of the book distinguishes four main concepts of culture, presenting their histories, uses, limitations and mutual contradictions, which else often tend to be neglected. The second part scrutinizes neomaterialist and posthumanist critics’ antihermeneutic efforts to escape the spirals of interpretation and meaning. Learning from such contestations, the third part summarizes the arguments and in five theses reconstructs a contemporary and comprehensive agenda for cultural studies, based on creative imagination and communicative mediation in the dynamic interface between meaning and materiality. This thus provides a survey of fundamental concepts and theories of culture for students and scholars in the humanities and social sciences, while simultaneously also serving as an introductory guide to the contemporary debate in this field.